2020
DOI: 10.1002/jcla.23192
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of preoperative lipid indices and their impact on new‐onset diabetes after liver transplantation

Abstract: Background The correlation between preoperative lipid profiles and new‐onset diabetes after transplantation (NODAT) remains relatively unexplored in liver transplant recipients (LTRs). Thus, we aimed to investigate the preoperative lipid profiles in Chinese LTRs and evaluate the different influences of preoperative total cholesterol, total triglycerides (TG), high‐density lipoprotein cholesterol, and low‐density lipoprotein cholesterol on the development of NODAT in both sexes. Methods A total of 767 Chinese L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…It is well established that in non-transplant patients, high levels of triglycerides are associated with an increased risk of type 2 diabetes, because ectopic lipid deposition in the liver, pancreatic islets, and skeletal muscle is responsible for β-cell dysfunction and worsening insulin resistance. A study with liver transplant patients showed a significant association between preoperative triglyceride levels and a higher incidence of PTDM, although only in men; an increment of 1 mmol/L in triglyceride levels increased the risk of PTDM by 37% (16).…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that in non-transplant patients, high levels of triglycerides are associated with an increased risk of type 2 diabetes, because ectopic lipid deposition in the liver, pancreatic islets, and skeletal muscle is responsible for β-cell dysfunction and worsening insulin resistance. A study with liver transplant patients showed a significant association between preoperative triglyceride levels and a higher incidence of PTDM, although only in men; an increment of 1 mmol/L in triglyceride levels increased the risk of PTDM by 37% (16).…”
Section: Discussionmentioning
confidence: 99%
“…As for general population, risk factors are Hispanic or African American ethnicity (1.6-fold increased risk), 150 male gender, older age, familiarity for diabetes, and metabolic risk factors (perisurgical blood glucose, 148 arterial hypertension, 153 and higher preoperative triglycerides, even within a near-normal range). 154 A recent meta-analysis pooling data from 37 studies showed that pre-LTx body mass index and overweight were associated with a higher risk of PTDM, while no association was found with post-LTx body mass index. 155 Notably, PTDM prevalence increases progressively in the posttransplant period, and in a single-center study of 415 adult LTx recipients, it was 34.7%, 46.9%, and 56.2% at 1, 3, and 5 y, respectively, with older age remaining as the only independent predictor.…”
Section: Introductionmentioning
confidence: 99%